Human Rights in Deuteronomy With Special Focus on Slave Laws - Tsai, Daisy Yulin (Berlin Boston De Gruyter, 2014)
This study compares two Deuteronomic slave laws with their counterparts adopting a multidimensional examination including classified subject matters, rhetorical techniques, and the rationale of legal philosophy. This approach sheds light on the similarity and differences between the biblical and ANE slave laws, as well as the basic concepts of human rights presented in Deuteronomy
Biographical note: Daisy Yulin Tsai, Logos Evangelical Seminary, El Monte, CA, USA.
This study compares two Deuteronomic slave laws with their counterparts adopting a multidimensional examination including classified subject matters, rhetorical techniques, and the rationale of legal philosophy. This approach sheds light on the similarity and differences between the biblical and ANE slave laws, as well as the basic concepts of human rights presented in Deuteronomy.
Legal Status and Treatments of Slaves
Description based upon print version of record
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Human Rights; Slavery in the Bible; Deuteronomy -- slave law -- human rights -- slavery; RELIGION / Christian Theology / General; RELIGION / Ancient; RELIGION / Biblical Criticism & Interpretation / Old Testament; Deuteronomy; slave law; Human Rights; Slavery; Electronic books; Hochschulschrift